The influence of male circumcision for HIV prevention on sexual behaviour among traditionally circumcised men in Cape Town, South Africa. - Eaton, L A; Cain, D N; Agrawal, A; Jooste, S; Udemans, N; Kalichman, S C (International journal of STD & AIDS, 2011)
We examined the relationship between HIV prevention beliefs related to male circumcision and sexual behaviour/sexually transmitted infection (STI) acquisition among traditionally circumcised men in Cape Town, South Africa. HIV-negative men (n = 304), circumcised for cultural/religious reasons, attending a health clinic in Cape Town, South Africa, completed cross-sectional surveys. Generalized linear models were used to analyse the relationships between unprotected vaginal sex acts, number of female sexual partners, STI diagnoses and male circumcision-related beliefs and risk perceptions. Men who were aware that circumcision offers protection against HIV (relative risk [RR] = 1.19, 95% confidence interval [CI] = 1.06-1.32, P < 0.01), endorsed risk compensation related to male circumcision (RR = 1.15, 95% CI = 1.11-1.12, P < 0.01) and perceived lower risk of HIV infection when circumcised (RR = 1.08, 95% CI = 1.04-1.12, P < 0.01) were more likely to report unprotected vaginal sex acts. Similar patterns were also identified when predicting number of female sexual partners. Men who were more likely to endorse risk compensation related to male circumcision were also more likely to be diagnosed with a chronic STI (odds ratio [OR] = 1.64, 95% CI = 1.06-2.53, P < 0.05). Our findings suggest that we must not overlook the effects of beliefs towards male circumcision for HIV prevention among men traditionally circumcised; doing so may undermine current efforts to reduce HIV transmission through male circumcision.
Keywords: Adult; Circumcision, Male; Cross-Sectional Studies; Female; Health Knowledge, Attitudes, Practice; HIV Infections; Humans; Male; Risk-Taking; Sexual Behavior; South Africa